Soteriology in Islam and Its Application to Contemporary Japan - Ko Nakata, Hassan (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Soteriology in Islam and Its Application to Contemporary Japan